-17+72=-5(x+2)

Simple and best practice solution for -17+72=-5(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -17+72=-5(x+2) equation:



-17+72=-5(x+2)
We move all terms to the left:
-17+72-(-5(x+2))=0
We add all the numbers together, and all the variables
-(-5(x+2))+55=0
We calculate terms in parentheses: -(-5(x+2)), so:
-5(x+2)
We multiply parentheses
-5x-10
Back to the equation:
-(-5x-10)
We get rid of parentheses
5x+10+55=0
We add all the numbers together, and all the variables
5x+65=0
We move all terms containing x to the left, all other terms to the right
5x=-65
x=-65/5
x=-13

See similar equations:

| 2=–c4 | | -18(x-9)=-324 | | 4x+2x-7=177 | | 2x+30=114 | | j/20=20 | | 12.5=2g=3.5 | | .5(3x-4)=11 | | 7x+27+60-5=180 | | 10-7g=-5-10g | | 15x+–19x−–8=–8 | | -2+16v=-26+4v | | 45x+20=12x+90 | | 2x+40=114 | | 4(3x+8)=-46+54 | | 83=n+-880 | | 3.1+10m=7.38 | | 22+6h=2(2h-3) | | t/4+15=14 | | |x|=7.19 | | 5(2x-3)=2x-16 | | 7+4j=19 | | 3x-28=28 | | -6n+36=24-8n | | 1+m/4=6 | | 35+30x=125x | | x+12=4(4x-6) | | p/3-17=-13 | | 5g=2(3g-1)=9 | | 3(m+2)-1=8 | | 9+2r=1 | | -8+n/26=-9 | | -28-6x=-4x-(7x-2) |

Equations solver categories